2010
DOI: 10.1186/1471-2458-10-104
|View full text |Cite
|
Sign up to set email alerts
|

Social network types and functional dependency in older adults in Mexico

Abstract: BackgroundSocial networks play a key role in caring for older adults. A better understanding of the characteristics of different social networks types (TSNs) in a given community provides useful information for designing policies to care for this age group. Therefore this study has three objectives: 1) To derive the TSNs among older adults affiliated with the Mexican Institute of Social Security; 2) To describe the main characteristics of the older adults in each TSN, including the instrumental and economic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
77
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 31 publications
5
77
1
2
Order By: Relevance
“…In Germany, no additional network types were found, but two sub-types for the friends-focused type emerged, "supported" and "unsupported", as well as two sub-types for the restricted groupings, "non-friend-unsatisfied" and "non-family-unsupported" (Fiori et al 2007). A unique "widowed" network grouping was found in Mexico (Doubova et al 2010). In Israel, two additional types found were the "community-clan" and "neighbors" networks (Litwin and ShiovitzEzra 2006).…”
Section: The Concept Of Social Network Typementioning
confidence: 87%
See 1 more Smart Citation
“…In Germany, no additional network types were found, but two sub-types for the friends-focused type emerged, "supported" and "unsupported", as well as two sub-types for the restricted groupings, "non-friend-unsatisfied" and "non-family-unsupported" (Fiori et al 2007). A unique "widowed" network grouping was found in Mexico (Doubova et al 2010). In Israel, two additional types found were the "community-clan" and "neighbors" networks (Litwin and ShiovitzEzra 2006).…”
Section: The Concept Of Social Network Typementioning
confidence: 87%
“…For example, belonging to different network types is related to depressive symptomatology (Fiori et al 2006) and to morale (Litwin 2001). Embeddedness in different network constellations is also associated with such physical health outcomes as visual difficulty and incontinence (Litwin 1998), functional dependency (Doubova et al 2010), and survival (Litwin and Shiovitz-Ezra 2006). Research has also shown that social network types are related to differing degrees of formal service utilization, such as public home care (Litwin 2004).…”
Section: The Concept Of Social Network Typementioning
confidence: 97%
“…The process of aging is characterized by a decrease in the physiological capacity, progressively declining functions of the organs and systems (Fulop et al, 2010), older adults presenting a natural progressive loss of physical capacities and a dysfunction of the musculoskeletal system by gradual changes in their body mass index (Rexhepi et al, 2011), as well as body composition, decreasing muscle mass and bone mineral density and increasing the body fat mass content (Rolland et al, 2009); These effects result in a unbalance of motricity, becoming more weak (Jang & Van Remmen, 2010;Doubova et al, 2010;Blain et al, 2010, Fraga et al, 2011Guzmán et al, 2011), predisposing the elderly to have lower functional autonomy in activities of daily living such as walking, climbing stairs, or rising from a chair without the help of a person or device (Molt et al, 2010;Reid et al, 2008;de Noronha et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the types of networks older adults create are culturally dependent and specific, showing differences between countries and across race, gender, and socioeconomic status (Cheng, Lee, Chan, Leung, & Lee, 2009;Doubova et al, 2010;Fiori et al, 2008;Litwin & Shiovitz-Ezra, 2006), it is important not to prioritize certain relationships over others. This may be critical for marginalized groups.…”
mentioning
confidence: 99%